INTEGRATING KNOWLEDGE: HEALTH LITERACY AND ITS EFFECT ON COMPLIANCE OF TYPE II DIABETES - Wahid, Muhammad Hassan; Shuaib, Mohammad Shumaq; Khan, Muhammad Vali; Ahmad, Mansoor; Muhammad Arsalan,; Ahmad, Waqar; Khan, Muhammad Aman (Journal of Postgraduate Medical Institute, 2023)
Objective: To find out the effect of Health Literacy (HL) on Treatment Adherence among Patients with Type II Diabetes Mellitus, covering both Pharmacological and Non-Pharmacological compliances. Methodology: This research was conducted using cross-sectional survey on patients with the mean age of 55.15+.59 years from Mercy teaching hospital of Peshawar from March to August 2022. Chronic Disease Self-Management Program (CDSMP) and another questionnaire related with knowledge, risk factors and its complications were also used. Control on diabetes of patients was measured by the last HBA1C test results. Analysis was carried out using SPSS v.26, using descriptive statistic and Pearson correlation. Results: In this study the response rate was 96.8%, with the mean age (n=242) of 55.15+.59 years. The Reliability of the scale Chronic Disease Self-Management Program (CDSMP) through Cronbach Alpha reliability was 0.88. Most of the patients were male (n=157, 64.8%), from OPD (n=238, 98%), and have diabetic family history (n=198, 80%) respectively. Majority of the patients were taking oral medications (n=135, 55.6%), have good diabetic control levels of HbA1c (n=104, 42.8%) and taken physician guide regarding diabetes knowledge and management (n=86, 35.4%) respectively. Statistically significant relationship was found between health literacy with pharmacological and non-pharmacological compliance (p=0.000) through Pearson correlation. Conclusion: It is concluded that a high level of HL plays a vital role in the management of type II diabetes, also it is strongly related with improved glycemic control, indicating a strong positive relationship between knowledge acquisition and successful management of diabetes.